Informativeness of experiments for MEU: a recursive definition - Heyen, Daniel; Wiesenfarth, Boris Roland (Journal of mathematical economics, 2015)
The well-known Blackwell theorem states the equivalence of statistical informativeness and economic valuableness. Çelen (2012) generalizes this theorem, which is well-known for subjective expected utility (seu), to maxmin expected utility (meu) preferences. We demonstrate that the underlying definition of the value of information used in Çelen (2012) is in contradiction with the principle of recursively defined utility. As a consequence, Çelen’s framework features dynamic inconsistency. Our main contribution consists in the definition of a value of information for meupreferences that is compatible with recursive utility and thus respects dynamic consistency.
Available online 10 December 2014
Gesehen am 14.09.2020